Perancangan Aplikasi Website Pengelolaan Surat Masuk dan Keluar Dengan Menggunakan Metode Design Thinking Studi Kasus: Rektorat UKDW - Priagung Satriyotomo; Mahastama, Aditya Wikan; Santosa, R. Gunawan (Fakultas Teknologi Informasi, 2024)
Letters are one of the most common forms of communication in people's daily lives. Activities related to letters are commonly referred to as correspondence. Duta Wacana Christian University Yogyakarta is one of the institutions where correspondence activities are still carried out for internal organizational purposes Initially, correspondence activities at UKDW were still done manually by using physical letters, which were sent to the intended address by asking people to deliver them directly. However, the correspondence process is becoming less efficient. The process that must be passed is quite long, so it takes a lot of time and energy. This incoming and outcoming lettters management website was designed to help and facilitate UKDW employees in carrying out correspondence activities, which were formerly performed manually, through the use of a website. This research uses design thinking as the design method. The Design Thinking method consists of several steps: Empathize, Define, Ideate, Prototype, and Testing. For the testing phase, the author uses the Usability Testing as a method to evaluate the effectiveness, efficiency, and user satisfaction of the website.